Legal Culture and Disability Rights in Indonesian Islamic Higher Education: A Review of Practices - Rismawati, Shinta Dewi; Mustakim, Zaenal; Mustakim, Zaenal; Mahmudah, Umi; Kamal, Rahmat (Journal of Ecohumanism, 2024)
This research aims to examine disability rights in relation to Islamic universities in Indonesia, paying attention to the legal culture concerning equal opportunities for disabled people. As a qualitative study with an empirical legal research method, this research will therefore gather information from various sources to examine current practices concerning regulations, facilities, and academic and social support, and disability education in Islamic higher learning institutions. The findings indicate that there is a major disparity between the legislation and the realities on the field. Implementation of strategies is poor, and a number of strategies are even ineffectual. Lack of physical infrastructure, academic accommodations, and training on the disability topics are some of the main challenges regarding full inclusion. Based on the study findings, it is suggested to enhance and expand the existing policies that include all parties and policies based on Islamic values that support equality and social justice. The final section reiterates the call for the reform of institutional culture and the advocacy of continuous public education to achieve cultural change.